Implementasi Model Pembelajaran Fisika Berbasis Nilai-Nilai Islam Pada SMA Kabupaten Pangkep - Nurhilaliyah; Dalilul Falihin (Referensi Islamika: Jurnal Studi Islam, 2024)
The Community Partnership Program (PKM) is implemented in Pangkep Regency - South Sulawesi Province. This was motivated by several Mitra problems, namely (1) Teachers' limited knowledge in utilizing physics lessons to integrate Islamic values; (2) Limited teacher skills in providing examples and examples of physics material based on Islamic values; (3) The need for teachers to prepare themselves in making flexible learning plans in integrating physics lessons with Islamic values. So, the aim of this activity is to resolve the Partner's problem. The methods used are counseling and teaching, discussion and training in collaboration between implementers and partners. This method is implemented for secondary school teachers throughout Pangkp Regency who register. The expected outcomes are: (1) Increasing teacher knowledge in utilizing physics lessons to integrate Islamic values; (2) Increasing awareness and knowledge among teachers about the importance of understanding and skills in providing examples and examples of physics material based on Islamic values; (3) Increasing teachers' insight, abilities and skills in preparing themselves to create flexible learning plans in integrating physics lessons with Islamic values; and (4) Reducing the number of poor teachers by integrating Islamic religious values ​​with physics materials. It is hoped that every physics teacher will be able to implement a physics learning model based on Islamic values.